(untitled) - FOS (Illinois, 1992)
This book builds step by step. Prat 1 covers the basic principles of refrigeration. Part 2 covers the use of refrigerants, including how to properly recycle and dispose of them. In part 3, the basic systems are introduced. The rest of the book covers testing, diagnosing, and servicing complete systems
Keywords: agricutural mechanics